Variations of perceived load and well-being between normal and congested weeks in elite case study handball team. Issue 3 (3rd July 2019) - Clemente, Filipe Manuel; Oliveira, Hugo; Vaz, Tiago; Carriço, Sandro; Calvete, Francisco; Mendes, Bruno
ABSTRACT: The aim of this study was two-fold: (i) to analyze the variations in internal load and well-being in professional handball players between normal and congested weeks and (ii) to analyze the variations between training days within weeks. Twenty male players (26.5 ± 4.9 yo) were monitored during a full season. MD-1 (match day −1) revealed larger decreases in muscle soreness (−17.3%, [−26.6;−6.9]) and fatigue (−16.6%, [−24.8;−7.4]) in congested weeks. Regarding MD-2, larger decreases in DOMS (−19.9%, [−30.5;−7.6]), fatigue (−19.7%, [−30.0;−7.9] and the Hooper index (−16.7%, [−25.6;−6.7]) were found in congested weeks. The results of this study reveal that larger variations between normal and congested weeks occurred in MD-2 and MD-3, with greater values of load and lower levels of well-being occurring in normal weeks. Within-weeks changes revealed greater loads occurring on MD-3 and MD-2 in comparison to MD-1; in the opposite way, greater values of muscle soreness and fatigue occurred on MD-1.